FORUM OF POLITICAL PARTIES, THINK TANKS AND NON-GOVERNMENTAL ORGANIZATIONS OF THE BRICS GROUP - E. Gladun (BRICS Law Journal, 2017)
The Joint International Forum of Political Parties, Think Tanks and NonGovernmental Organizations of the BRICS took place in Fuzhou, China on 10–12 June 2017. The event was hosted jointly by the International Department of the Central Committee of the Communist Party of China, the China Council for BRICS Think Tank Cooperation and the China NGO Network for International Exchanges.For the first time in the story of BRICS cooperation the countries’ representatives witnessed the renewed format of the BRICS Academic Forum – two traditional tracks (academic conference and civil track) were supplemented by the assembly of political parties. Taking its turn in chairing the multinational BRICS association in 2017, China proposed this new Forum format and joined together three dialogues that had grown out of the BRICS Academic Forum, which took place now for the ninth time.1 Another innovation on China’s part was the outreach format – representatives of 28 countries, including Indonesia, Malaysia, the Philippines, Cambodia, Egypt, Nigeria, Ethiopia, Kenya, Argentina, Chile and Mexico among others took part.The Joint International Forum was a truly large-scale international event – 37 political parties of 26 countries, 105 think tanks, and over 400 representatives of 79 civil society organizations were in attendance.2The Forum participants engaged in separate deliberations at the BRICS Academic Forum on “Pooling Wisdom and New Ideas for Cooperation,” the BRICS Civil Society Organizations Forum on “Stronger People-to-People Bond for Better Cooperation,” and the BRICS Political Parties Dialogue on the “Guiding Role of Political Parties in Promoting Cooperation.” The Forum was a complete success with broad consensus.